Fennen und Finnen : Tacitus' Fennenschilderung im Vergleich mit Lappenschilderungen späterer Zeiten - Milan, Karl (2001)
The Fe1mians, described by the Roman historian Publius Comelius Tacitus in his work Germania (98 AD), are commonly considered to be the Baltic-Finnish ancestors of the present-day Finns (Suomi-Finns; Suomi = Finland). This argumentation is based not only on the shared name, but also on their geographical location which scholars consider to coincide exactly with the areas inhabited by the then Finns. When comparing the description by Procopius of the Scrithiphini – commonly considered by the scientific community to have been Lapps - to that of the Fennians by Tacitus, the clear similarities in the two descriptions attracted my attention. Therefore I started to study whether the later accounts - which definitely concern the Lapps – have somethit1g in common with the description of the Fennians by Tacitus. These comparisons, which constitute the principal part of my study, seem undeniably to show that everything written on the Lapps over the centuries is clearly coherent with the description by Tacitus. To provide further evidence for my interpretation, I wanted to present certain other statements and the respective argumentation. Certain experts have insisted that - on the basis of linguistic and archaeological evidence - the cultural level of the Baltic Finns, contemporary to Tacitus, was far superior to that of the Fennians. The traditional outlit1it1g of the livit1g area of the Fennians has been shown to be without any foundation. lt would have been impossible for Tacitus, considering his contemporary knowledge of the Nordic regions, to locate his Fennians in the areas where they actually belonged, i.e., the northern and eastern parts of Fenno-Scandinavia. Contrary to the common belief, Fennians and the Finni referred only to Lapps until late Middle Ages. Tue name Finni was transferred to the ancestors of the present Films only after they had become the inhabitants of the land of the Finni, i.e., the Lapps. The name Lapp became established during that period of time to denote the original Finni. Whilst studying and considering the above issues, I have become convinced that in the last chapter of Germania, Tacitus provides an extremely accurate and reliable account of the living conditions, customs and character of the Lapps. Tue role of the Suomi-Finns is limited to the fact that they are mentioned by a name that they have assumed fairly late and that some of the Fennians by Tacitus had inhabited the areas of the present Finland.